Implementasi Struktur Aljabar Besar Pada Reaksi Kimia: Reduksi – Oksidasi - Fakhry Asad Agusfrianto; Yudi Mahatma (Universitas Negeri Gorontalo, 2023)
Algebraic Hyperstructures is a generalization of the concept of algebraic structure. One of the concepts on algebraic hyperstructures is hypergroups. The concept of hypergroups can be generalized into hypergroupoids, hypersemigroups and -groups. Hypergroups and their generalization have applications in science fields such as chemistry, biology, and physics. The focus of discussion in this paper is the application of hypergroups and their generalization in the field of chemistry. In basic chemistry, we know chemical reactions called reduction and oxidation (redox) reactions. The purpose of this paper is to analyze the algebraic hyperstructures contained in redox reactions.